314 Mapping preeclampsia inequalities in medical treatment: Converging medicare/medicaid and clinical trial availability - Olivia Diaz; Terry Church (Journal of Clinical and Translational Science)
Objectives/Goals: This study looks to better understand and call attention to the inequalities found within medical treatment options for individuals suffering from preeclampsia during pregnancy in the USA. The goal is to map the terrain of clinical trials and evaluating existing medicare/medicaid covered services on a both national and state levels. Methods/Study Population: The study population for this research was limited to: pregnant women, ages 18–45, both pregnant and postpartum suffering from preeclampsia. We began looking at clinical trials targeting preeclampsia treatment conducted within the United States between 2019 and 2024. Using our study population parameters, we searched clinicaltrials.gov. These trials’ inclusionary and exclusionary factors were noted, along with participant race. The drug intervention medication used during these clinical trials was compared to those prescribed by doctors via the current national standard of care. We then looked at Medicaid coverage provided to expecting mothers on a state-to-state basis and nationally regulated level. These factors included coverage on ultrasounds, low-dose aspirin, blood pressure monitors, and more. Results/Anticipated Results: Preliminary findings demonstrate the need for more federally regulated policies and programs set in place to help combat the lack of resources faced by expecting mothers across the nation. This research will expose factors contributing to a lack of successful and completed clinical trials and lack of drug intervention innovations taking place to combat the rise in maternal deaths. This study will also focus on the importance of more education and awareness for communities such as African American mothers and those facing multiple gestational pregnancies who are at much higher risk of complications during their pregnancies. We also anticipate a large correlation between a lack of proper childbirth education and mothers who experience complications during birth. Discussion/Significance of Impact: Within the past two decades, rates of preeclampsia have grown 25% within the USA. It affects 5–8% of all pregnancies, and with maternal death rates rising, it is crucial to highlight the alarming lack of government regulation. It is imperative to provide awareness to mothers from disadvantaged backgrounds to treat this preventable condition.